Performance analysis of UWB-TR receiver - XIANG Xin1; WANG Yong-chao1; YI Ke-chu1; TIAN Hong-xin1 (Tongxin xuebao)
Based on the determination of UWB-STR receiver model,the performance of UWB-STR receiver was ana-lyzed by using a Gaussian approximation of the noise components at the output of the receiver and the analytical expres-sions of bit error rate（BER） performance were derived.The result shows that the receiver performance of BER is relevant to not only signal-to-noise ratio,but also input noise bandwidth and integration time.The characteristics can be applied to other kind of autocorrelation receivers.Finally,the analytical expressions of BER were compared with that in existing literatures and some results were modified.In addition,the expressions of BER for UWB-ATR receiver were given.